"When I'd Dealt with My Issues, I Was Ready to Give Back": Peer Leader's Perspectives of Support Groups for Women Abused by Intimate Partners. Issue 2 (7th February 2017) - Tutty, Leslie M.; Ogden, Cindy; Wyllie, Karen; Silverstone, Andrea
ABSTRACT: The serious nature of the abuse of women by intimate partners has garnered worldwide concern. Victims are often assisted through support groups; however, little is known about how the groups work or how leaders perceive the group process and the women's response to the intervention. This qualitative process evaluation presents the perspectives of 14 trained peers who led weekly Growth Circle groups to provide support to abused women. The article describes the leader's backgrounds, perceptions of the group process, and coleadership, in addition to reflections on the value and challenges in offering the program. Implications for community agencies and group leaders are offered.